Substituting for the State: Informal Institutions, Retrospective Regularization, and the Limits of Formal Supervision in Indonesian Seaweed Aquaculture - Suhadi Suhadi; Badu Ahmad; Muh. Akmal Ibrahim; Didik Iskandar (Journal Social Civilecial, 2025)
The social-ecological systems (SES) framework treats boundary clarity, formal rules, monitoring, sanctions, and institutional capacity as interdependent attributes of durable commons governance and generally assumes that informal institutions complement or nest within formal ones. This article examines a case in which informal institutions instead substitute for formal provision across all five attributes at once. Seaweed cultivation in Nunukan Regency, on Indonesia’s maritime border with Malaysia, expanded from 2,652 to 13,050 ha between 2018 and 2023. Drawing on 71 semi-structured interviews with 62 informants across three coastal sub-districts and four administrative tiers, together with document review, we find every formal attribute weak: no legally enacted zoning, seven of nine regulatory domains without specific rules, no licence held by any of nineteen cultivators interviewed, none of eight water-quality parameters monitored on a schedule, and no formal sanction ever imposed for zoning breach. Informal institutions fill each gap, but unevenly. Substitution is dense in one sub-district, concentrated in a single village in a second, and has collapsed in a third. Two conceptual contributions follow. First, substitution is not a stable equilibrium: it depends on individual leadership and enforceable social sanction, and where either is absent no governance operates at all. Second, we identify retrospective regularization boundaries in practice follow where cultivators place their frames, and the state subsequently ratifies the result which converts spatial planning from a preventive instrument into a legitimating one. Aggregate claims that informal institutions compensate for weak states therefore obscure sharply divergent local outcomes.